The importance of e-learning in crisis management and its impact on internal efficiency from viewpoint of secondary school teachers in North Gaza Governorate, Palestine (Palestine Technical College Journal for Research and Studies, 2022)
The study aimed to identify the importance of e-learning in crisis management and its impact on internal efficiency from the point of view of secondary school teachers in North Gaza Governorate in Palestine. To achieve the objectives of the study, a questionnaire consisting of 30 items was developed distributed over three areas and distributed to 5 schools electronically, they were selected by random method. The study reached many results, the most important was: female teachers' attitudes in general are moderate towards using e-learning, and that female teachers have medium aptitude. The results showed that the field of e-learning importance in crisis management obtained an arithmetic average (3.41) and a relative weight (68.22) and a medium degree of appreciation, and the field of e-learning effectiveness got a medium effectiveness and an arithmetic average (3.47) and a relative weight of (69.39). E-learning in raising the internal efficiency at a medium grade, with a mean of (3.53), and with a relative weight of (70.50). The study also concluded that the use of e-learning increases communication with others and distinguishes herself from the rest of the teachers, through mastering computer and internet skills. Based on the results, the two researchers presented a set of recommendations, the most important of which are: the importance of training and encouraging female teachers and students on how to use e-learning in secondary schools in order to enhance and develop education in all circumstances and the teacher’s assistance to the student in exploiting the various school activities and presenting them via the electronic cloud.
Keywords: e-learning; internal efficiency; crisis management; secondary education; Palestinian female teachers